2021
DOI: 10.7759/cureus.17792
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Torsion: A Retrospective Analysis From a Tertiary Care Teaching Hospital in Northern India

Abstract: BackgroundAdnexal torsion is an acute gynecological emergency presenting with acute abdomen which can be missed owing to non-specific symptoms. Among reproductive-age women, conservative surgery is preferred. The present study was a retrospective analysis of adnexal torsion cases reported to a tertiary care teaching hospital in Northern India. The purpose of the study was to describe the demography, clinical features, diagnostic and treatment modalities, and prognosis of adnexal torsion cases. MethodsSurgicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The postoperative autopsy specimen in this case showed that the cyst fluid was dark brown, which may have caused intra-tumor bleeding due to rupture of small blood vessels in the cyst and rapid increase in tumor volume. [4] In practice, patients with ovarian cystic torsion have different clinical presentations due to different tumor characteristics and degrees of blood flow obstruction, which can easily lead to misdiagnosis and missed diagnosis. To improve the accuracy of ovarian cysts with tip torsion, Pierre P et al proposed a self-assessment questionnaire dedicated to gynecologic emergencies (SAQ-GE), which includes 5 independent predictors of AT diagnosis, which was used to assign a score of 3 for unilateral abdominal or low back pain, 2 for absence of abnormal leukorrhea and uterine bleeding, 2 for pain in the adnexal region, 2 for intolerable pain, and 1 for vomiting, for a total of 10 points for the diagnosis of AT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative autopsy specimen in this case showed that the cyst fluid was dark brown, which may have caused intra-tumor bleeding due to rupture of small blood vessels in the cyst and rapid increase in tumor volume. [4] In practice, patients with ovarian cystic torsion have different clinical presentations due to different tumor characteristics and degrees of blood flow obstruction, which can easily lead to misdiagnosis and missed diagnosis. To improve the accuracy of ovarian cysts with tip torsion, Pierre P et al proposed a self-assessment questionnaire dedicated to gynecologic emergencies (SAQ-GE), which includes 5 independent predictors of AT diagnosis, which was used to assign a score of 3 for unilateral abdominal or low back pain, 2 for absence of abnormal leukorrhea and uterine bleeding, 2 for pain in the adnexal region, 2 for intolerable pain, and 1 for vomiting, for a total of 10 points for the diagnosis of AT.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative autopsy specimen in this case showed that the cyst fluid was dark brown, which may have caused intra-tumor bleeding due to rupture of small blood vessels in the cyst and rapid increase in tumor volume. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…OT is considered a rare condition accounting for around 2.7% of gynecological surgical emergencies [ 3 ], and around 3% of ED visits presenting with abdominal discomfort [ 5 ]. Few studies have investigated the incidence of OT in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the gold standard for the diagnosis of OT remains by laparoscopic surgical exploration, pelvic ultrasonography with color doppler is the diagnostic imaging of choice [ 5 , 27 ]. In fact, the sensitivity of ultrasonography to detect OT was found to range from 70%-72% and the specificity from 87%-99.6% [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation